Project-based learning in biology: exploring its contribution to improving students' science process skills - Cesaria, Gusermi Ananta; Darussyamsu , Rahmawati; Alberida, Heffi; Fitri, Rahmadhani (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
The Project-Based Learning (PjBL) model has been widely applied in biology learning to encourage students' science process skills. However, the extent of its contribution to improving science process skills has not been thoroughly summarized. Therefore, this study aims to analyze the impact of the PjBL model on science process skills using a meta-analysis. Through a systematic literature review using the PRISMA approach, seven journal articles and theses were selected that met the inclusion criteria. The effect size for each study was calculated using Cohen's d. The analysis showed that all studies had very large effect sizes, ranging from 1.67 to 5.35. This finding indicates that PjBL consistently improves science process skills such as observing, classifying, predicting, measuring, inferring, and communicating. The syntax of PjBL, which involves real, structured activities, also optimally supports the development of these skills. Thus, PjBL can be recommended as an effective learning approach to improve students' science process skills in biology.